2017
DOI: 10.1111/bjd.15647
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake and risk of nonmelanoma skin cancer: a systematic review and dose–response meta‐analysis

Abstract: Nonmelanoma skin cancer (NMSC) comprises mainly basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC). The association between alcohol intake and NMSC has been inconclusive; therefore the objective of this study is to quantify the relationship between alcohol intake and NMSC using meta-analyses. A systematic literature search of PubMed and Embase was performed on 30 October 2016. Eligible articles were case-control or cohort studies that examined alcohol intake and risk of BCC or cSCC and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 55 publications
2
28
2
1
Order By: Relevance
“…The results of Yen and colleagues are consistent with those published in a meta‐analysis investigating the relationship between alcohol drinking and melanoma risk . However, current evidence is insufficient to conclude for a causal association between alcohol intake and skin cancer, both melanoma and NMSC, as residual confounding by UVR and other unknown factors cannot be completely ruled out .…”
supporting
confidence: 57%
See 3 more Smart Citations
“…The results of Yen and colleagues are consistent with those published in a meta‐analysis investigating the relationship between alcohol drinking and melanoma risk . However, current evidence is insufficient to conclude for a causal association between alcohol intake and skin cancer, both melanoma and NMSC, as residual confounding by UVR and other unknown factors cannot be completely ruled out .…”
supporting
confidence: 57%
“…For each alcoholic drink per day, the risk of BCC increased by 7%, and that of SCC by 11%. The risk did not significantly differ by sex for both BCC and SCC, and a positive association was observed only in cohort studies, and for studies located in the U.S.A …”
mentioning
confidence: 79%
See 2 more Smart Citations
“…We observed a relatively small difference in life expectancies across different levels of alcohol consumption compared with other individual lifestyle factors. The cardiovascular benefits of moderate alcohol consumption have been consistently observed in large cohort studies,40 but alcohol consumption and risk of cancer showed a dose-response relation 4142. Thus, current guidelines do not encourage a non-alcohol drinker to start drinking just for the benefit of preventing cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%